Perkembangan Aneka Warna Hukum (Rechtbedeling) di Indonesia: Pluralisme Hukum Waris di Indonesia - ; Carwan (Syntax Idea)
As a result of the existence of Article 131, jo, article 163 IS, the Law of Inheritance regulated in the Civil Code applies to Europeans and those who are equal to these Europeans. The impact of enacting population classification rules and laws applicable to each group during the Dutch colonial period. The problem in this paper is how the development of various colours of law (Rechtbedeling) in Indonesia and how the pluralism of inheritance law in Indonesia related to the development of multiple shades of law. The research method used is normative legal research and legal history. The results showed that the division of the Indonesian population based on ethnicity and class emerged during the Dutch colonial occupation. This was enacted for political interests during the Dutch colonial career in Indonesia, namely by issuing rules for classifying the population and the laws that apply to each group based on the provisions of Article 131 jo. Article 163 lS creates Pluralism of Inheritance Law, where European and Chinese groups in Indonesia are regulated in the Civil Code. For indigenous people who are not Muslims, customary inheritance law applies. In contrast, for those who are Muslims, Islamic inheritance law applies, and foreigners other than Chinese use their respective customary inheritance laws. So, the unification of inheritance law is needed to eliminate societal conflicts because the heirs are subject to different inheritance laws.